Colombia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper examines conditions in Colombian labor markets, which present a big challenge to the country. At end-2004, the unemployment rate amounted to 12 percent, and about one-third of the labor force was considered underemployed. The paper reviews labor market developments leading up to the reforms. It examines structural issues in the labor markets, reviews the labor market reforms, and analyzes the impact of reforms versus stronger growth. The paper also analyzes various aspects of Colombia's system of intergovernmental transfers.